Anxiety, depression and coronary artery disease among patients undergoing angiography in Ghaem Hospital, Mashhad, Iran - Tajfard, Mohammad; Ghayour-Mobarhan, Majid; Rahimi, Hamid Reza; Mouhebati, Mohsen; Esmaeily, Habibollah; Ferns, Gordon A. A.; Abd Latiff, Latiffah; Tajfiroozeh, Farzaneh; Mokhber, Nagmeh; Nazeminezhad, Ramin; Falsoleyman, Homa; Taghipour, Ali; et al. (Scientific Research Publishing, 2014)
The prevalence of coronary artery disease (CAD) is increasing in Iran. Patients with depression who have a myocardial infarction are more likely to die and patients who have depressive symptoms during hospitalization may have increased cardiovascular events. This study aimed to determine the relationship between anxiety, depression and coronary artery disease among patients undergoing angiography in Ghaem Hospital, Mashhad. This was a case-control study conducted between September 2011 and August 2012 among patients undergoing coronary angiography in Ghaem Hospital, Mashhad, Iran. There were 486 cases that were found to have one or more coronary stenoses, with a stenosis of equal or more than 50% of the diameter of at least one major coronary artery. The other patient group consisted of the patients in whom the coronary artery stenosis was less than 50% in diameter which was classified as angiography negative, and a control group that consisted of 440 healthy adults aged 18 years old and above who were selected among people who attended for routine medical checkup and medical examination of employment. The dependent variables were Beck Anxiety and Depression Inventory scores and the independent factors were coronary artery disease, and socioeconomic profiles. Validated and reliability-tested questionnaires were used for data collection. The mean age of patients was 55.75 ± 10.64 years and in the healthy group was 55.83 ± 8.55 years; there was no significant difference in age between subject groups (p = 0.897) nor a significant difference in the gender frequency distribution of subjects (p = 0.610). There was a significant difference in anxiety score between the Angio positive and Angio negative patients and healthy control subjects (p < 0.001). There was a statistical significant difference between groups for the anxiety score (p < 0.001). However, the subjects did not differ significantly for BDI depression score (p = 0.534). A significant positive relationship was found between anxiety score and depression score when data were analyzed by Pearson’s test (p < 0.001, Pearson’s correlation = 0.582). Depression and anxiety are associated among patients with CAD undergoing coronary angiography sessions.